2014
DOI: 10.1093/hmg/ddu333
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies susceptibility loci of silica-related pneumoconiosis in Han Chinese

Abstract: Pneumoconiosis is the most serious occupational disease in China and its leading cause is occupational silica exposure. Pneumoconiosis takes several years to develop depending on the exposure level of silica. However, individual variation in the susceptibility to pneumoconiosis has been observed among the subjects with similar exposure. We conducted a genome-wide screening with 710,999 single nucleotide polymorphisms (SNPs) in a cohort of 400 coal workers (202 cases and 198 exposed controls) for pneumoconiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…This study has several merits. Previous studies have clearly shown that silica dust exposure is associated with SPF risk, and that silica dust exposure‐based matching can be effective in controlling for potential confounding effects when studying genetic susceptibility . In the current study, all cases and controls in each stage (except GSE80555) were matched by years of silica dust exposure, which may considerably increase the possibility of identifying potential biomarkers.…”
Section: Discussionmentioning
confidence: 97%
“…This study has several merits. Previous studies have clearly shown that silica dust exposure is associated with SPF risk, and that silica dust exposure‐based matching can be effective in controlling for potential confounding effects when studying genetic susceptibility . In the current study, all cases and controls in each stage (except GSE80555) were matched by years of silica dust exposure, which may considerably increase the possibility of identifying potential biomarkers.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic factors can influence the susceptibility and/or severity of CWP. Indeed, a series of genetic factors have been documented in association with initiation and development of CWP, including genes modulating inflammatory and immune responses [6,8]. Interaction of GITR with GITRL could up-regulate conventional T cell responses and down-regulate T reg suppressor activity, thus upset the balance and result in a breakdown of autoimmune response and immunological tolerance [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…prolonged lung inflammation and fibrotic nodular lesions that usually lead to progressive fibrosis [5]. Although silica dust exposure is recognized as the primary cause of pneumoconiosis, extensive researches indicate that genetic factors have played important roles in the development of pulmonary fibrosis [2,[6][7][8]. During the past four decades in China, CWP continues to occur even though work environment and prevention measures have been greatly improved [9], and still more than 23 million workers exposed to silica particles [10].…”
Section: Introductionmentioning
confidence: 99%
“…No genomic markers, however, have been validated to date . This includes potential susceptibility loci from genome‐wide association studies (GWAS, rs73329476, rs4320486 and rs117626015), and the T1559C/rs5368 polymorphism . Regarding TNF‐α, the TNF‐α‐308A allele has been linked to ever having CWP especially with nodules as opposed to PMF, whereas TNF‐α promoter TNF2 polymorphism has been associated with the development of large opacities .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%